Transport chain analysis, projection and international distribution of manufacturing paint encouraging in the integrity of the goods - Lopez Molina, Alex (2009)
There is a Ecuadorian Paint Enterprises who has long been a leader in paint processing and selling in the early 1980¨s. Recently has appear a international corporation located in Colombia who has spread theirs operation to Ecuador and integrated the firm to its supply chain. Related to this new environment, the firm is hammering away at its top line as well, working to increase revenues by delivering more high products to the international markets. The logistics staff went to basics, the search for improvement opportunities took on a new sense of deliver, and now a renewed passion for achieving an optimized international delivered operation. The methodology is set in order to define at the beginning each link of the transport chain. The next step is improve the actual operation by an optimizing model and allowing automatic systems for the handling and shipping process through the whole analysis of the data. Once achieved the transport chain model, there will be a key link for further simulations and internationals trades bringing operational expertise to these projects in addition to knowledge of restrictions, regulations and contract needs.